Development of Process Automation System for Structural Design of the Wind Turbine Gearbox - Dong Huimin; Han Mengke; Qiu Jun; Wang Delun; Liang Shiwen; Jia Ping (Jixie chuandong)
The current experience-dominated structural design process separates the structural design from CAE analysis in the development of a new wind turbine gearbox,which leads to a quite long-term development cycle and the redundancy of structural materials.Consequently,a new structural design process is presented based on topological optimization theory and combined with CAE.Through a secondary development for Hyperworks with C# and TCL / TK language,a new process automatic system characterized by lightweight structure for the structural design of wind turbine gearboxes is developed.The operability of the system is testified by the instance of designing a planet carrier.The case indicates that the process automatic system can lead designers to finish the lightweight-oriented structural design for wind turbine gearbox parts,and the pre and post processing efficiency can increase by 90% than the current process,and the development cycle of new products of wind turbine gearbox is shorten enormously.